Huquq al-insan wa al-khitabat al-diniyyah : (Markaz al-Qahirah li-Dirasat Huquq al-Insan, 2006)
'Human rights and religious rhetoric : how do we benefit from the experiences of the non-Arab Islamic world?' Islam.